2013
DOI: 10.1051/epjconf/20135914003
|View full text |Cite
|
Sign up to set email alerts
|

Iron and Nickel spectral opacity calculations in conditions relevant for pulsating stellar envelopes and experiments

Abstract: Abstract. Seismology of stars is strongly developing. To address this question we have formed an international collaboration, OPAC, to perform specific experimental measurements, compare opacity calculations, and improve the opacity calculations in stellar codes [1]. We consider the following opacity codes: SCO, CASSANDRA, STA, OPAS, LEDCOP, OP, SCO-RCG. Their comparison has shown large differences for Fe and Ni in equivalent conditions of envelopes of type II supernova precursors, temperatures between 15 and … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Essential considerations of astrophysical opacity computations are accuracy and completeness in the treatment of the radiative absorption processes, both difficult to accomplish in spite of the powerful computational facilities available nowadays. As reviewed in Section IV, it has been shown that configuration interaction (CI) effects are noticeable in the spectrum shape in certain thermodynamic regimes for the topical cases of Cr, Fe, and Ni [16,19,21], while incomplete configuration accounting leads to sizable discrepancies in others [33]. To rigorously satisfy both requirements with the OP R-matrix method for isoelectronic sequences with electron number N > 13, it implies close-coupling expansions that soon become computationally intractable and must then be tackled with simpler CI methods (e.g., AUTOSTRUCTURE) that neglect the bound-continuum coupling.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Essential considerations of astrophysical opacity computations are accuracy and completeness in the treatment of the radiative absorption processes, both difficult to accomplish in spite of the powerful computational facilities available nowadays. As reviewed in Section IV, it has been shown that configuration interaction (CI) effects are noticeable in the spectrum shape in certain thermodynamic regimes for the topical cases of Cr, Fe, and Ni [16,19,21], while incomplete configuration accounting leads to sizable discrepancies in others [33]. To rigorously satisfy both requirements with the OP R-matrix method for isoelectronic sequences with electron number N > 13, it implies close-coupling expansions that soon become computationally intractable and must then be tackled with simpler CI methods (e.g., AUTOSTRUCTURE) that neglect the bound-continuum coupling.…”
Section: Discussionmentioning
confidence: 99%
“…The OPAC international consortium [14,17] has been carrying out extensive comparisons using a battery of opacity codes (SCO, CASSANDRA, STA, OPAS, LEDCOP, OP, and SCO-RCG), looking into the importance of configuration interaction and accounting mainly in elements of the iron-group bump (Z bump), i.e., Cr, Fe, and Ni, due to their relevance in the pulsation of intermediate-mass stars. In this respect, the magnitude of the Fe and Ni contributions to the Z-bump and the temperature at which they occur have been shown to be critical in p-and g-mode pulsations in cool subdwarf B stars [72,73].…”
Section: Atomic Opacities Recent Developmentsmentioning
confidence: 99%